Accountability and platforms' governance: The case of online prominence of public service media content - Krisztina Rozgonyi (Internet Policy Review, 2023)
Public discourse has moved online, enabled by platforms, which in the context of information and media content have become an essential source, access point and key distributor of information. Public Service Media (PSM) - the 'basic information service provider' with a special mandate from the state - increasingly relies on platforms under the universality principle to reach out and interact with the broadest range of their audiences. However, control over PSM content dissemination and audience engagement is primarily determined by the private interest-ruled platforms via algorithmic recommendation systems (content curation) and according to their terms and conditions (community standards). This paper addresses the necessity and possibilities of safeguards for PSM content delivery on digital online platforms as an issue of media pluralism. Actual or potential policy interventions for the preferential treatment of public value content, aka due prominence online, were studied through the analytical lens of accountability in its interaction with platforms and PSM performance. Finally, the analyses on the appropriateness of the current accountability regimes for achieving pluralism objectives laid out recommendations for future policy for public-interest-driven platform governance.
Keywords: 300; Platform governance; Media; Accountability; Content filtering; Media pluralism